Pengaruh Penambahan Berbagai Level Konsentrat Mengandung ZnSO4 dan Zn-Cu Isoleusinat terhadap Penggunaan Protein Kambing Kacang yang Mengkonsumsi Silase Sorgum – Kembang Telang - Cesilia Wilfrida Seran; Erna Hartati; Gusti Ayu Yudiwati Lestari (Universitas Nusa Cendana, 2021)
The purpose of this study was to determine the optimal addition of various levels of concentrate containing ZnSO4 and Zn-Cu isoleusinat against the use of protein that consumes sorghum-kembang telang silage in goats kacang. This study used 12 goats Kacang with an average body weight of 14.40 kg (KV = 14.93%). This study used a Randomized Block Design (RBD) with 4 treatments and 3 replications. The four treatments were T1 = Silage sorghum-kembang telang ad libitium, and T2, T3, T4 = T1 + concentrate with levels of 10%, 20% and 30% respectively containing 150 mg ZnSO4 and 2% Zn-Cu Isoleucine. The parameters observed were PK consumption, PK digestibility, and blood urea concentration. The results showed that the addition of various levels of concentrate containing ZnSO4 and Zn-Cu isoleusinat which was optimal for the use of protein that consumed sorghum-kembang telang silage in goats Kacang had a significant effect (P <0.05) on crude protein consumption, but had no significant effect (P <0.05) on crude protein digestibility and blood urea concentration. The conclusion is that the addition of various levels of concentrate containing ZnSO4 and Zn-Cu isoleusinat which is optimal for the use of protein that consumes sorghum-kembang telang silage in goats Kacang is found in T4 treatment as much as 30%.